Identification of ɤ-Aminobutyric Acid (GABA) in Loloh as A Potential Drink as Antihipertension - I Gusti Ayu Wita Kusumawati; Ni Made Indri Sugiantari; I Gede Ariyasa; Ida Bagus Agung Yogeswara (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Loloh sembung (Blumea balsamifera) is a functional drink that is widely consumed by Balinesse people and exhibit health-promoting effect. The purpose of this study was to identify GABA of loloh sembung which has physiological effect as antihypertensive. Proximate analysis was performed to determine nutritional value content of loloh sembung. Atomic Absorption Spectrophotometric (AAS) method was employed to determine potassium and sodium content, and identificatio of ɤ-aminobutyric acid (GABA) using Thin Layer Chromatography (TLC) method. In this study, water content of loloh sembung was 99.2324%, ash 0.0117. Fresh sembung leaves have water content 83.8112%, ash content 2.0617%, protein 0.9659%, fat 2.850%, and carbohydrate 10.3109%. Loloh sembung contained sodium, 51.65 mg/L and potassium 1353.10 mg/L. Subsequently, fresh sembung leaves contained sodium 579.72 mg/L and pottasium 1353.19 mg/L respectively. In this study, GABA was detected in loloh sembung and has promising prospect as antihypertensive-functional drink.